Purchase intention towards edible bird's nest product among different groups of Malaysian consumers - Mohamad Shukri, Nurul Nabilah Huda (2020)
Edible bird’s nest (EBN) is a glutinous mucilaginous secretion produced by the salivary glands of male Swiftlets. Until today, EBN has been consumed as a health supplement to restore human body deficiency by supplying nutrients. The beneficial effects of EBN on human health proclaimed by traditional Chinese medicine practitioners have been proven with all the lab research conducted by previous studies. A growing number of investors and ranchers are being attracted to venture into the Swiftlet farming business because this industry possesses higher market value and is viewed as a million-dollar industry. This industry could be a new source of wealth and contribute to Malaysian economic growth. In 2011, this industry has experienced in price slump due to the high nitrate level found in raw EBN. This has significantly tarnished Malaysia’s image. All ranchers and investors in this industry felt the vast impact from the price declination of EBN. As the contamination found in EBN has caused the price to fall steeply, the issue of adulteration in EBN with haram-related sources appears to be an ongoing discussion. These issues further heighten the fear and anxiety among consumers to consume EBN products. As a result, ranchers failed to survive since local EBN products could not be exported to China and also due to relatively low demand for EBN products in Malaysia. Therefore, this study aims to compare the difference in intention level between the groups of buyer and non-buyer, identify factors that influence intention to purchase and repurchase EBN products among non-buyers and buyers in Malaysia, discover potential and existing consumers, and investigate the differences between buyers based on their spending behaviours.